Towards understanding SNS fatigue: exploration of social experience in the Virtual World - Yamakami, T. (2012 8th International Conference on Computing and Convergence Technology, 2012)
The rise of social network services (SNSs) has brought an emerging need of understanding the virtual world from social contexts. The stay time of SNSs is increasing worldwide. Billion-scale virtual world social interactions are realized and has impacted multiple aspects of human lives. One notable negative aspect of SNSs is SNS fatigue. People are heavily involved in SNSs and some show SNS fatigue or SNS burnouts. The author compiles the reasons that users left SNSs. Then, the author discusses the three factors that impact forming attitudes, a two-dimensional classification of SNS departures in different contexts, and a tree-diagram view that parses the process of SNS departures.